DETERMINANTS OF CAPITAL STRUCTURE OF PLANTATION COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Chairul Azman; Ristati; Yusniar; Chairil Akhyar (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study aims to determine the determinants of the capital structure of plantation companies on the Indonesia Stock Exchange. The data used in this research is secondary data from 22 plantation companies during the research period from 2017 to 2021 so that the observations in the study totaled 110 observations. The method used to analyze the relationship between the independent variables and the dependent variable is the panel data regression method. The results showed that partially Tangibility had a positive and significant effect on capital structure in Plantation Companies on the Indonesia Stock Exchange, Profitability had a positive and significant effect on capital structure in Plantation Companies on the Indonesia Stock Exchange, and Liquidity had a positive and significant effect on capital structure in Plantation Companies on the Indonesian Stock Exchange.